Research on the Construction of Time and Space by Short Video with TikTok as the Representative from the Perspective of Media Affordance - Dong, Hangchi (International Journal of Social Sciences and Public Administration, 2024)
From the perspective of Affordance, this paper discusses how short video platforms represented by TikTok construct time and space, and analyzes the mechanism and influence behind it. Media availability theory emphasizes the possibilities and scope of action that specific media technologies can provide for individuals, and how these technological characteristics shape human behavior. In the short video field, especially on the Douyin platform, media availability is not only reflected in the generation, dissemination, and consumption of video content but also profoundly affects users ’perception and experience of time and space.